Implementing ICT into language and law classroom to develop law students’ communicative competence - Юлінецька, Юлія Василівна; Юлінецька, Ю. В.; Юлинецкая, Юлия Васильевна; Yulinetska, Yuliia V.; Yulinetskaya, Yuliya V.; Бабій, Оксана Юріївна; Бабій, О. Ю.; Бабий, Оксана Юрьевна; Babii, Oksana Yu.; Гловюк, Ірина Василівна; Гловюк, І. В.; Гловюк, Ирина Васильевна; et al. (Information Technologies and Learning Tools, 2021)
The new context of changes in labour-market requirements calls for development of foreign language communication competence and use of technologies that promote professional life-long learning. Individual characteristics necessary for a professional to integrate into the international socio-cultural environment have recently been challenged particularly because of growing demands to the ability to communicate, be autonomous and responsible for the achieved learning outcomes. A switch of the European higher education content to the competence-based learning contributes to the development of the mentioned characteristics and competence. Further, the National Qualifications Framework of Ukraine (7 Level, Second cycle (Master)) envisages mastering foreign language communicative competence in professional activities. This research addresses the issue of ICT tools application in the development of foreign language communicative competence of law students during individual study. We focus on blended learning model, which is combination of traditional and distance learning approaches. To conduct the research, focus groups were defined and examined; relevant authentic material (the VOTA, HUDOC database, and CURIA case-law database) analysed; and the most appropriate ICT tools established. The department of foreign languages of the National University "Odessa Academy of Law" designed, tested, piloted and uploaded the on-line dictionary "gLAWssary"; developed and recorded the video course "Legal English in Use" which is offered on the university website. The results indicate that the on-line dictionary and video course supplemented by the workbook are powerful tools to promote professional life-long learning and that individual study skills are central to this task. This finding suggests that a thoroughly elaborated course with the relevant ICT tools could be the basis for building foreign language communicative competence of future lawyers.

Зміни вимог ринку праці передбачають розвиток навичок комунікації іноземною мовою та використання технологій, що сприяють постійному професійному навчанню. Індивідуальні навички, що необхідні професіоналу для інтеграції в міжнародне соціальнокультурне середовище, уже зазнали змін через постійне зростання попиту на людей, що вміють спілкуватися, бути незалежними та нести відповідальність за результати навчання. Зміна змісту європейської вищої освіти на навчання на базі компетентностей сприяє розвитку зазначених навичок та компетенцій. Більше того, Національні рамки кваліфікації України (7-ий рівень, другий (магістерський)) передбачають використання іноземних мов у професійній діяльності. Дослідження присвячене питанню застосування інструментів ІКТ (інформаційно-комунікаційних технологій) у розвитку компетенції спілкування іноземною мовою майбутніх юристів під час індивідуального навчання. Увага зосереджена на змішаній моделі навчання, що є комбінацією традиційного та дистанційного підходів до навчання. З метою проведення дослідження були вивчені фокус-групи, проаналізований відповідний автентичний матеріал (VOTA, база даних HUDOC та база судових рішень CURIA), визначені найбільш відповідні інструменти ІКТ. Кафедра іноземних мов Національного університету «Одеська юридична академія» розробила, протестувала, та завантажила онлайн словник «gLAWssary»; організувала та записала відеокурс «Legal English in Use», що розміщений на вебсторінці університету. Отримані результати свідчать про те, що індивідуальні навички навчання є центральними у досягненні вказаної мети, а онлайн словник та відеокурс разом з робочим зошитом виступають потужними інструментами для сприяння постійному професійному навчанню. Результати свідчать, що ретельно розроблений курс, разом з належними інструментами ІКТ, може бути базисом для побудови компетенції володіння іноземними мовами майбутніми юристами.

Изменения требований рынка труда предусматривают развитие навыков коммуникации на иностранном языке и использование технологий, которые способствуют постоянному профессиональному обучению. Индивидуальные умения, которые необходимы профессионалу для интеграции в международную социально-экономическую среду, уже претерпели изменения, в частности, из-за стойкого роста спроса на людей, которые умеют общаться, быть независимыми и нести ответственность за результаты обучения. Переход содержания европейского высшего образования к обучению на базе компетентностей способствует развитию указанных умений и компетенций. Более того, Национальные рамки квалификации Украины (7-ой уровень, второй (магистерский)) предусматривают использование иностранных языков в профессиональной деятельности. Исследование посвящено вопросу использования инструментов ИКТ (информационнокоммуникационных технологий) в развитии компетентностей общения на иностранном языке будущих юристов при индивидуальноом обучении. Внимание сосредоточено на смешанной модели обучения, которая является комбинацией традиционного и дистанционного подходов к обучению. С целью проведения исследования были изучены фокус-группы, проанализирован соответствующий аутентичный материал (VOTA, база данных HUDOC и база судебных решений CURIA), а также определены наиболее соответствующие инструменты ИКТ. Кафедра иностранных языков Национального университета «Одесская юридическая академия» разработала, протестировала и загрузила онлайн словарь «gLAWssary»; организовала и записала видеокурс «Legal English in Use», который размещен на веб-странице университета. Полученные результаты свидетельствуют о том, что индивидуальные умения обучения являются центральными в достижении указанной цели, а онлайн словарь и видеокурс вместе с рабочей тетрадью являются мощными инструментами, которые способствуют постоянному профессиональному обучению. Результаты свидетельствуют о том, что тщательно разработанный курс вместе с надлежащими инструментами ИКТ могут выступать базисом для построения компетенции владения иностранными языками будущих юристов.
Yulinetskaya Yu. V. Implementing ICT into language and law classroom to develop law students’ communicative competence / Yu. V. Yulinetskaya, O. Yu. Babii, I. V. Hloviuk, A. S. Stepanenko, M. I. Pashkovskyi // Information Technologies and Learning Tools. - 2021. - Vol 81. - No1. - P. 310-326.
Keywords: blended learning model; ICT tools; competence-based approach; foreign language; individual study; law students; змішана модель навчання; інструменти ІКТ; компетентнісний підхід; іноземна мова; індивідуальне навчання; майбутні юристи; модель смешанного обучения; инструменты ИКТ; компетентностный подход; иностранный язык; индивидуальное обучение; будущие юристы; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education